A Salivation Abnormality with Trigeminal Nerve Dysfunction in Dogs. (March 2019) - Kent, Marc; Song, Rachel B.; Glass, Eric N.; de Lahunta, Alexander
Trigeminal nerve pathology can lead to sensory and motor dysfunction to structures of the head that are easily recognized. The trigeminal nerve is a conduit for the distribution of postganglionic parasympathetic innervation to structures of the head. Parasympathetic innervation to the salivary glands is provided by preganglionic parasympathetic neurons of the facial and glossopharyngeal nerves. Postganglionic axons course with branches of the mandibular branch of the trigeminal nerve to reach the salivary glands. Denervation of the salivary glands impacts glandular function, leading to a reduction in the volume and composition of the saliva produced. Saliva plays an important role in oral health. Poor oral health has widespread systemic implications. This article describes a group of dogs with unilateral or bilateral dysfunction of the trigeminal nerve and/or its branches. In all dogs, an accumulation of thick, foamy saliva was observed accumulating in the dorsal aspect of the caudal oral cavity on the ipsilateral side to the affected nerve. In dogs with magnetic resonance imaging (MRI), there was a reduction in size based on the largest cross-sectional area measurement and an increase in mean signal intensity of the salivary glands ipsilateral to the affected nerves compared to the glands on the normal side. The authors hypothesize that the abnormal saliva and MRI changes observed were consequent to parasympathetic denervation of the salivary glands. The recognition of this clinical observation is the first step in understanding the impact that denervation has on salivation and ultimately on overall oral and systemic health in dogs.